Gradiometer based on two single-hole SQUIDs; IEEE Transactions on Instrumentation and Measurement; Vol. 39, iss. 6 - Likhachev A. G.; Polushkin V. N.; Uchaykin S. V. Sergey Victorovich; Vasiliev B. V. (1990, 1990)
Title screen